Pengaruh Perjanjian Pra-Nikah terhadap Komposisi dan Pembagian Harta Warisan dalam Perspektif Hukum Perdata Indonesia - M. Sifa Fauzi Yulianis; Didit Darmawan; Yusril Pratama Hidayat; Muhammad Hind Hisyam; Cyntia Varashenna Zabella; Afriezal Muhammad Dafa; Tri Budiarto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2026)
Abstract A prenuptial agreement is a legal instrument that provides prospective husbands and wives with the flexibility to determine the distribution of assets during the marriage. The existence of such an agreement has a significant impact on the composition and distribution of inheritance, as it directly limits the scope of acquired assets, joint assets, and the proceeds from asset development. From the perspective of civil law and marriage law in Indonesia, a prenuptial agreement serves as a means to ensure legal certainty and prevent disputes in the inheritance distribution process. This study aims to examine the position of prenuptial agreements within the national marriage law system and explore their impact on potential inheritance disputes. The research findings indicate that the provisions regarding the separation or consolidation of assets outlined in a prenuptial agreement will determine the composition of the inheritance upon the death of one spouse. If no agreement is made, all assets acquired during the marriage are classified as joint assets, whereas if an agreement is made, acquired assets and personal assets remain outside the scope of joint assets. However, problems often arise due to the lack of clear regulations regarding the status of certain assets, such as the development of inherited assets, or because the agreement does not meet the requirements of the Civil Code, such as not being drawn up by a notary deed or not being registered with a marriage registrar. This situation often gives rise to disputes between heirs and with interested third parties. Thus, a prenuptial agreement serves not only as a mechanism for separating assets but also as a preventative instrument to protect the rights of heirs and strengthen legal certainty in the inheritance process.